Digital Watermarking 9th International Workshop, IWDW 2010, Seoul, Korea, October 1-3, 2010, Revised Selected Papers - Kim, Hyoung-Joong.; Shi, Yun Qing.; Barni, Mauro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th Interntaional Workshop on Digital Watermarking, IWDW 2010, held in Seoul, Korea, in October 2010. The 26 revised full papers presented were carefully reviewed and selected from 48 submissions. The papers are organized in topical sections on forensics, visual cryptography, robust watermarking, steganography, fingerprinting, and steganalysis.
Keywords: Computer science; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Information storage and retrieval systems; Computer graphics; Computer vision; Computer Science; Data Encryption; Data Structures, Cryptology and Information Theory; Coding and Information Theory; Information Storage and Retrieval; Computer Graphics; Image Processing and Computer Vision